Redes de cooperação para o desenvolvimento tecnológico no setor de biotecnologia - Santos, Bruno Rodrigues dos (2023)
Brazil is one of the countries with the greatest biodiversity in the world, presenting more than 20% of the total number of species on the planet. This abundant variety of plants and animals has great potential for biotechnological development and exploitation. This study aimed to analyze the trends of Brazilian research on biotechnology-biodiversity binomial, seeking to better improve trends, frequencies and terminologies in publications and/or research groups with the use of the binomial. In the first stage of this study, a bibliographic review was carried out in the Google Scholar database, between May and June 2020, using the keywords "Brazil and biotechnology or biodiversity" and their corresponding ones in English, for articles published from 2015. The first 200 research results were analyzed. In the second stage, a secondary search was carried out on the database of the Directory of Research Groups of the Lattes Platform of CNPQ. In the third stage, the text data mining approach was carried out with the Voyant program, in order to better identify trends in the biodiversity-biotechnology interface in the texts found in the database and in the directory. The analysis of content through word cloud made it possible to verify that in the literature in general the binomial biodiversitybiotechnology is discussed more broadly, mainly about the possibility of development in various sectors, through the design of products and processes and the need for constant incentive and investment in research. On the other hand, the research groups discuss the binomial biodiversity-biotechnology in a more specific way, especially around the areas of application of biotechnology and the products arising from the forms of exploitation of biodiversity through biotechnology. From this literature review, it is possible to verify the correspondence between the scientific production published and considered relevant by the research instrument and the objectives of the researchers who compose the research groups certified in the Lattes platform in relation to the biodiversity interface – biotechnology, given the competition of subjects and works in both parties. In general, the trend is identified as an increasingly intense need to expand knowledge about biodiversity, in order to find solutions to the most diverse existing problems, seeking to improve biotechnology applied in health, agriculture, industry, aiming at improving the quality of life and biodiversity conservation through sustainable development.